The enhancement of ammonium removal from ethanolamine wastewater using air-cathode microbial fuel cells coupled to ferric reduction. (August 2015) - Shin, Ja-Won; Seo, Seok-Ju; Maitlo, Hubdar Ali; Park, Joo-Yang
Highlights: Alcohol group of ETA was effectively degraded in an air-cathode single-chamber MFC. Adding goethite in MFC with acetate and ammonium increased the ammonium removal. The maximum power density of the MFC with goethite and ETA was 210 mW m −2 . Abstract: A microbial fuel cell (MFC) with biological Fe(III) reduction was implemented for simultaneous ethanolamine (ETA) degradation and electrical energy generation. In the feasibility experiment using acetate as a substrate in a single-chamber MFC with goethite and ammonium at a ratio of 3.0 (mol/mol), up to 96.1% of the ammonium was removed through the novel process related to Fe(III). In addition, the highest voltage output (0.53 V) and maximum power density (0.49 W m −2 ) were obtained. However, the ammonium removal and electrical performance decreased as acetate was replaced with ETA. In the long-term experiment, the electrical performance markedly decreased where the voltage loss increased due to Fe deposition on the membranes.